The farnesyl transferase inhibitor RPR-130401 does not alter radiation susceptibility in human tumor cells with a K-Ras mutation in spite of large changes in ploidy and lamin B distribution - Mégnin-Chanet, Frédérique (BioMed Central, 2002)
BACKGROUND: Growth inhibition by RPR-130401, a non-peptidomimetic farnesyltransferase inhibitor, was investigated without or with combined exposure to ionizing radiation in three human tumor cell lines (HCT-116, MiAPaCa-2 and A-549) bearing a point mutation in the K-Ras gene. RESULTS: RPR-130401 inhibited cell growth with an IC(50) of 50 nM (HCT-116), 120 nM (MiAPaCa-2) and 710 nM (A-549), with a poor incidence of apoptosis. The drug brought about G1 and S phase depletion together with arrest of cells in G2 phase and induced a significant accumulation of hyperploid cells showing active S phase DNA synthesis, with HCT-116 and A-549 cells being the most and least responsive, respectively. The drug also produced dramatic changes of the nuclear lamin B pattern, without lamin B cleavage and perturbation of the actin cytoskeleton. On the other hand, RPR-130401 elicited strictly additive interaction in combined treatment with ionizing radiation with regard to cell kill, altered cell cycle progression and induced hyperploidy. CONCLUSIONS: The data suggest that disruption of orderly progression through mitosis and cytokinesis, is a major outcome of drug action and that this effect proceeds from inhibition of lamin B farnesylation. It is anticipated from the strict additivity of RPR-130401 and radiation that neither induced radiation resistance nor acute or late complications of radiotherapy, should occur in combined treatment with RPR-130401.